Doing Business in the House of God: Negotiation Space between Worship and Economics on Friday Prayer - Muhammad Yafiz (IBDA` : Jurnal Kajian Islam dan Budaya, 2016)
This article describes about Â negotiation space between worship and economics on Friday prayer at Masjid Ulul Albab (MUA) Medan. The main focus on this research is the appearance of pedagang kagetan (sudden traders) on Friday pray laying down their merchandises such as worship equipments, Moslem clothing, meal, snack, mineral water, etc around the mosque. The findings of this articles is the phenomenon where there is Â there is a change Â function of the mosque becomesÂ  a market. To understand the phenomenon, there are two questions appear: Â what are the factors that contribute to the negotiations of worship and the economy and how the practice of economic progress. This paper explains that the factors pushing this situation becauseÂ  there is Â â€œblurringâ€ between the room of worship and economic boundaries. ThusÂ  there is dominance of economic Â in the worship space. It happens because there is mutual need between merchants and pilgrims. It is done to meet the needs of the merchant family.